High-toughness and low-swelling ionic conductive hydrogel as well as preparation method and application thereof

CN119409992AActive Publication Date: 2025-02-11NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI +1

Patent Information

Application Number
CN202411768458.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Existing ionic conductive hydrogels have shortcomings in terms of mechanical strength, working range, toughness and swelling properties, especially in the problems of repeated deformation and swelling in aqueous solutions.

Method used

By dissolving acrylic acid, acrylamide, phytic acid and sodium carboxymethylcellulose in deionized water, removing bubbles, adding initiator and crosslinking agent to perform radical polymerization, a high strength, tough, low swelling ionic conductive hydrogel was prepared. .

Benefits of technology

The high strength and toughness, low swelling and good conductivity of the hydrogel are achieved, and can maintain high sensitivity within the range of tensile strain 0-800%, and the low swelling performance in seawater has broadened its application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409992A_ABST
    Figure CN119409992A_ABST
Patent Text Reader

Abstract

The invention discloses high-toughness low-swelling ionic conductive hydrogel and a preparation method and application thereof, and belongs to the technical field of polymer hydrogel, and the preparation method comprises the following steps: dissolving acrylic acid, acrylamide, phytic acid and sodium carboxymethyl cellulose in deionized water, and uniformly mixing to obtain a precursor solution; removing bubbles in the precursor solution to prepare a bubble-removed precursor solution; adding an initiator and a cross-linking agent into the bubble-removed precursor solution, and stirring until the initiator and the cross-linking agent are completely dissolved to obtain a pre-polymerized solution; and carrying out free radical polymerization on the pre-polymerized solution under a preset condition to obtain the high-toughness and low-swelling ionic conductive hydrogel. Through the synergistic enhancement effect of phytic acid and carboxymethyl cellulose, the multifunctional ionic conductive hydrogel is developed, and the hydrogel has excellent mechanical properties, can realize low swelling in water and artificial seawater, and also has good conductivity. The preparation method is simple, controllable in operation and easy for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer hydrogels, and in particular relates to a high-toughness, low-swelling ion conductive hydrogel, a preparation method and an application thereof. Background Art

[0002] Ion-conductive hydrogels have shown significant potential in the field of flexible bioelectronics due to their excellent flexibility, conductivity, and mechanical compatibility with biological tissues; among them, flexible wearable sensors have become the focus of research due to their ability to monitor physiological signals and movements in real time. Ion-conductive hydrogels have unique stretch-sensitive properties, and their resistance changes according to the applied tensile strain, making them ideal materials for building flexible wearable sensors.

[0003] However, although a variety of flexible wearable strain sensors based on ion-conductive hydrogels have been developed, these materials show good sensitivity in signal detection, but they still have the limitations of insufficient mechanical strength, narrow working range and low toughness. In addition, repeated deformation during use will significantly impair their signal detection capabilities; and the high swelling properties of ion-conductive hydrogels are also one of the main limitations of their development.

[0004] Since ion-conductive hydrogels are usually made of hydrophilic materials far from the swelling equilibrium state, most of them tend to swell in aqueous solutions during their applications; although the three-dimensional cross-linked structure usually prevents the hydrogel network from disintegrating during swelling, the volume expansion of the hydrogel can significantly reduce its mechanical and conductive properties, severely limiting its application.

[0005] At present, achieving high mechanical properties and low swelling has become the key requirement for ion conductive hydrogels. Therefore, the ideal ion conductive hydrogel for flexible wearable sensors should have high strength and toughness, fatigue resistance, low swelling, a wide working range, and maintain good mechanical properties and conductive properties after swelling, in addition to good sensitivity. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a high-toughness, low-swelling ion-conductive hydrogel.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a high-toughness, low-swelling ion-conductive hydrogel, comprising:

[0010] Dissolve acrylic acid, acrylamide, phytic acid and sodium carboxymethyl cellulose in deionized water, mix well, and obtain a precursor solution;

[0011] removing bubbles from the precursor solution to obtain a precursor solution from which bubbles are removed;

[0012] Adding an initiator and a cross-linking agent to the precursor solution from which bubbles have been removed, stirring until completely dissolved, to obtain a prepolymer solution;

[0013] The prepolymer solution is free radical polymerized under preset conditions to obtain an ion conductive hydrogel with high strength, toughness and low swelling.

[0014] As a preferred embodiment of the preparation method of the present invention, the free radical polymerization method includes at least one of temperature-induced free radical polymerization and light-induced free radical polymerization.

[0015] As a preferred embodiment of the preparation method of the present invention, the concentration of acrylic acid in the precursor solution is 2.5-4 mol / L, the concentration of acrylamide in the precursor solution is 1-2.5 mol / L, the concentration of phytic acid in the precursor solution is 0.2-0.4 mol / L, and the concentration of sodium carboxymethyl cellulose in the precursor solution is 5-18 mg / mL.

[0016] As a preferred embodiment of the preparation method of the present invention, the initiator is 0.05-0.4 mol% of the total molar amount of acrylic acid and acrylamide.

[0017] As a preferred embodiment of the preparation method of the present invention, the initiator comprises a free radical polymerization initiator selected from at least one of ammonium persulfate, potassium persulfate and 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0018] As a preferred embodiment of the preparation method of the present invention, the cross-linking agent comprises a cross-linking agent having a double bond at the terminal group, which is selected from at least one of polyethylene glycol diacrylate and N,N'-methylenebisacrylamide.

[0019] As a preferred embodiment of the preparation method of the present invention, the cross-linking agent is 0.05-0.2 mol% of the total molar amount of acrylic acid and acrylamide.

[0020] Another object of the present invention is to overcome the deficiencies in the prior art and provide an ion conductive hydrogel with high strength and low swelling, wherein the elongation at break of the hydrogel is 875-1082%, the tensile stress at break is 0.53-2.05 MPa, and the toughness during stretching is 2.19-10.57 MJ / m 3 ;

[0021] When the compression reaches 80% strain, the compressive stress is 3.53-8.00 MPa and the compression modulus is 352.68-663.28 kPa;

[0022] The swelling rate of the hydrogel in water is 100% to 150%;

[0023] The tensile elongation at break of the hydrogel after swelling in water is 612-805%, and the tensile stress at break is 326-613 kPa;

[0024] The swelling rate of the hydrogel in artificial sweat is 160-215%;

[0025] The swelling rate of the hydrogel in artificial seawater is 8.0% to 20.5%;

[0026] The conductivity of the ion conductive hydrogel is 1.06 to 2.39 S / m.

[0027] Another object of the present invention is to overcome the deficiencies in the prior art and provide an ion-conductive hydrogel with high strength and low swelling for use in a sensor, wherein: the sensor includes a flexible sensor.

[0028] Another object of the present invention is to overcome the deficiencies in the prior art and provide an ion conductive hydrogel with high strength and low swelling for use in the preparation of wearable devices.

[0029] Beneficial effects of the present invention:

[0030] (1) The present invention develops a multifunctional ion conductive hydrogel through the synergistic enhancement of phytic acid and carboxymethyl cellulose. The gel has excellent mechanical properties, low swelling in water and artificial seawater, and good conductivity. The preparation method is simple, the operation is controllable, and it is easy to industrialize.

[0031] (2) In the ion conductive hydrogel provided by the present invention, the poly(acrylic acid-co-acrylamide) molecular chains and the rigid chains of carboxymethyl cellulose form a double network structure, and phytic acid, poly(acrylic acid-co-acrylamide) and carboxymethyl cellulose form a physical cross-linking structure through hydrogen bonding. On the one hand, the strong hydrogen bonding interaction between phytic acid and the poly(acrylic acid-co-acrylamide) molecular chains induces the stable phase separation of poly(acrylic acid-co-acrylamide), and the rigid chains of carboxymethyl cellulose and the poly(acrylic acid-co-acrylamide) molecular chains form a double network, which further enhances the mechanical properties and fatigue resistance of the hydrogel. On the other hand, the strong hydrogen bonding interaction between phytic acid and carboxymethyl cellulose can inhibit the attraction of phytic acid to water molecules and the diffusion of phytic acid molecules, thereby reducing the swelling performance of the hydrogel and obtaining a low swelling hydrogel.

[0032] (3) The ion conductive hydrogel provided by the present invention exhibits high sensitivity in the tensile strain range of 0-800%, and the low swelling in seawater can further broaden the application scenarios of the hydrogel and expand the working range of the hydrogel; in addition, the introduction of phytic acid not only gives the hydrogel excellent conductivity and strain sensing ability, but also gives the hydrogel significant antifreeze, antibacterial and biocompatibility properties, showing great application potential in multifunctional wearable smart sensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0034] Figure 1 Schematic diagram of the preparation of the hydrogel in the embodiment of the present invention.

[0035] Figure 2 The tensile performance curves of the hydrogels of Example 1 and Comparative Examples 1 to 4 of the present invention are shown.

[0036] Figure 3 The compression performance curves of the hydrogels of Example 1 and Comparative Examples 1 to 4 of the present invention are shown.

[0037] Figure 4 This is a comparison chart of the swelling properties of the hydrogels of Example 1 of the present invention and Comparative Examples 1 to 3 in water.

[0038] Figure 5 This is a diagram showing the swelling performance of the hydrogel of Example 1 of the present invention in different solutions.

[0039] Figure 6It is a graph showing the conductivity performance of the hydrogels of Example 1 and Comparative Examples 1 to 4 of the present invention.

[0040] Figure 7 Graph showing the relative resistance change (ΔR / R0) and gauge factor (GF) of the hydrogel of Example 1 of the present invention under the condition of tensile strain of 0-800%.

[0041] Figure 8 This is a graph of the cyclic conductivity stability of the hydrogel of Example 1 of the present invention under a tensile strain of 100%.

[0042] Fig. 9 This is a diagram of the mixing results of Comparative Example 5 of the present invention. DETAILED DESCRIPTION

[0043] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0044] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0045] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0046] The polyethylene glycol diacrylate used in the present invention has an average molecular weight of about 575 and is a common commercial product; other raw materials are all common commercial products.

[0047] The test conditions of the performance in the embodiments of the present invention are:

[0048] Mechanical properties: Mechanical testing of the hydrogels was performed using a universal testing machine;

[0049] The hydrogel samples were cut into dumbbell shapes (gauge length of 25 mm, width of 4 mm, and thickness of 2 mm) for tensile testing and stretched at a rate of 50 mm / min until the breaking point, and the toughness was calculated by the area under the stress-strain curve;

[0050] For compression testing, the hydrogel samples were cut into cylindrical shapes (10 mm in diameter and 5 mm in thickness) and compressed at a rate of 0.5 mm / min until 80% strain, and the elastic modulus (E) was calculated from the slope of the fitting line in the linear range of the stress-strain curve.

[0051] Swelling properties: The hydrogels were cut into samples with a diameter of 10 mm and a thickness of 2 mm;

[0052] Each sample was immersed in deionized water or artificial sweat or artificial seawater at room temperature until equilibrium swelling was achieved. The mass of the swollen hydrogel was measured at regular intervals and the swelling ratio was calculated using the following equation:

[0053] Swelling ratio = ((W s -W0) / W0)*100%

[0054] Where W s and W0 are the weights of the swollen hydrogel and the original hydrogel, respectively.

[0055] Conductive properties: The hydrogel was cut into samples with a size of 50 mm × 5 mm × 2 mm;

[0056] The conductivity of the hydrogel was measured using a digital four-probe tester. A universal testing machine was used to apply different tensile loads to the hydrogels, and their resistance changes were recorded simultaneously through an electrochemical workstation;

[0057] Calculate the change in resistance (ΔR / R0) using the following formula:

[0058]

[0059] Here, R0 and R are the resistances when no strain is applied and when strain is applied, respectively.

[0060] Calculate the Gauge Factor (GF) using the following formula:

[0061] GF = (ΔR / R0) / ε, where ε is the tensile strain.

[0062] Example 1

[0063] (1) dissolving acrylic acid (4 mol / L), acrylamide (1 mol / L), phytic acid (0.4 mol / L), and sodium carboxymethyl cellulose (11.1 mg / mL) in deionized water and mixing well to obtain a precursor solution;

[0064] (2) treating the precursor solution with ultrasound for 10 min to remove bubbles;

[0065] (3) Adding an initiator 2-hydroxy-2-methyl-1-phenyl-1-propanone (0.3 mol%) and a crosslinker polyethylene glycol diacrylate (0.1 mol%) to the above solution, stirring until completely dissolved to obtain a prepolymer solution, and irradiating the prepolymer solution under ultraviolet light for 60 minutes to obtain the ion conductive hydrogel through free radical polymerization.

[0066] The hydrogel preparation method is as follows Figure 1 shown.

[0067] The test results of the universal testing machine showed that the elongation at break of the hydrogel in this embodiment was 1082%, the tensile fracture stress was 2.05MP, and the toughness during stretching was 10.57MJ / m 3 ,like Figure 2 As shown;

[0068] When the compression reaches 80% compression strain, the compression stress is 8.00MPa and the compression modulus is 663.28kPa. Figure 3 shown.

[0069] like Figure 4 As shown, the swelling rate of the hydrogel in water in this embodiment is only 100%, showing a good anti-swelling effect.

[0070] Moreover, the swelling rate of the hydrogel in artificial sweat was about 160%, and the swelling rate in artificial seawater first increased to 40% and then decreased, and the final swelling rate was only 8%, showing a good anti-swelling effect. The increase in the initial swelling rate may be caused by the high salt ion concentration in artificial seawater. Figure 5 .

[0071] The conductivity of the hydrogel in this example is 2.39 S / m, see Figure 6 ;

[0072] Further experiments found that the hydrogel maintained good sensitivity in the tensile strain range of 0-800%, with the strain factor GF value increasing from 0.95 (≤150%) to 1.84 (150-300%) and 2.23 (≥300%), showing a wide sensing range. Figure 7 .

[0073] At the same time, 200 100% strain stretching loading and unloading cycles were applied to the hydrogel, and it was found that the hydrogel could maintain a continuous and stable resistance signal during the test, showing excellent strain sensing fatigue resistance. Figure 8 .

[0074] Example 2

[0075] (1) dissolving acrylic acid (3.8 mol / L), acrylamide (1.2 mol / L), phytic acid (0.38 mol / L), and sodium carboxymethyl cellulose (18.0 mg / mL) in deionized water and mixing well to obtain a precursor solution;

[0076] (2) treating the precursor solution with ultrasound for 15 min to remove bubbles;

[0077] (3) adding an initiator ammonium persulfate (0.4 mol%) and a cross-linking agent N,N'-methylenebisacrylamide (0.1 mol%) to the above solution, stirring until completely dissolved to obtain a prepolymer solution, and the prepolymer solution is placed in a 60°C water bath for 24 hours to obtain the ion conductive hydrogel through free radical polymerization.

[0078] The elongation at break of the hydrogel in this embodiment is 945%, the tensile fracture stress is 1.83MP, and the toughness during stretching is 9.27MJ / m 3 ;

[0079] When the compression reaches 80% compression strain, the compressive stress is 7.53MPa and the compression modulus is 603.16kPa; the swelling rate in water is 112%, the swelling rate in artificial sweat is 178%, and the swelling rate in artificial seawater is 9.5%; the conductivity is 2.14S / m.

[0080] Example 3

[0081] (1) dissolving acrylic acid (3.5 mol / L), acrylamide (1.5 mol / L), phytic acid (0.35 mol / L), and sodium carboxymethyl cellulose (15.3 mg / mL) in deionized water and mixing well to obtain a precursor solution;

[0082] (2) treating the precursor solution with ultrasound for 15 min to remove bubbles;

[0083] (3) Adding an initiator 2-hydroxy-2-methyl-1-phenyl-1-propanone (0.35 mol%) and a crosslinker polyethylene glycol diacrylate (0.05 mol%) to the above solution, stirring until completely dissolved to obtain a prepolymer solution, and irradiating the prepolymer solution under ultraviolet light for 30 minutes to obtain the ion conductive hydrogel through free radical polymerization.

[0084] The elongation at break of the hydrogel in this embodiment is 921%, the tensile fracture stress is 1.48MP, and the toughness during stretching is 7.83MJ / m 3 ; When the compression reaches 80% compression strain, the compression stress is 7.06MPa and the compression modulus is 564.19kPa;

[0085] The swelling rate in water is 129%, the swelling rate in artificial sweat is 184%, and the swelling rate in artificial seawater is 11.3%; the conductivity is 2.01S / m.

[0086] Example 4

[0087] (1) dissolving acrylic acid (3.3 mol / L), acrylamide (1.7 mol / L), phytic acid (0.3 mol / L), and sodium carboxymethyl cellulose (12.4 mg / mL) in deionized water and mixing well to obtain a precursor solution;

[0088] (2) treating the precursor solution with ultrasound for 20 minutes to remove bubbles;

[0089] (3) Adding an initiator 2-hydroxy-2-methyl-1-phenyl-1-propanone (0.25 mol%) and a crosslinker polyethylene glycol diacrylate (0.15 mol%) to the above solution, stirring until completely dissolved to obtain a prepolymer solution, and irradiating the prepolymer solution under ultraviolet light for 30 minutes to obtain the ion conductive hydrogel through free radical polymerization.

[0090] The elongation at break of the hydrogel in this embodiment is 912%, the tensile fracture stress is 1.03MP, and the toughness during stretching is 5.87MJ / m3; when the compression reaches 80% compression strain, the compressive stress is 6.28MPa, and the compression modulus is 519.23kPa;

[0091] The swelling rate in water is 134%, the swelling rate in artificial sweat is 191%, the swelling rate in artificial seawater is 13.8%, and the conductivity is 1.82S / m.

[0092] Example 5

[0093] (1) dissolving acrylic acid (3 mol / L), acrylamide (2 mol / L), phytic acid (0.25 mol / L), and sodium carboxymethyl cellulose (10.1 mg / mL) in deionized water and mixing well to obtain a precursor solution;

[0094] (2) treating the precursor solution with ultrasound for 25 min to remove bubbles;

[0095] (3) adding an initiator potassium persulfate (0.2 mol%) and a cross-linking agent N,N'-methylenebisacrylamide (0.15 mol%) to the above solution, stirring until completely dissolved to obtain a prepolymer solution, and the prepolymer solution is placed in a 50°C water bath for 48 hours to obtain the ion conductive hydrogel through free radical polymerization.

[0096] The elongation at break of the hydrogel in this embodiment is 890%, the tensile fracture stress is 0.86MP, and the toughness during stretching is 4.92MJ / m 3 ;

[0097] When the compression reaches 80% compression strain, the compressive stress is 5.72MPa and the compression modulus is 467.24kPa; the swelling rate in water is 139%, the swelling rate in artificial sweat is 203%, and the swelling rate in artificial seawater is 14.6%; the conductivity is 1.66S / m.

[0098] Example 6

[0099] (1) dissolving acrylic acid (2.8 mol / L), acrylamide (2.2 mol / L), phytic acid (0.22 mol / L), and sodium carboxymethyl cellulose (7.4 mg / mL) in deionized water and mixing well to obtain a precursor solution;

[0100] (2) treating the precursor solution with ultrasound for 25 min to remove bubbles;

[0101] (3) adding an initiator potassium persulfate (0.1 mol%) and a cross-linking agent N,N'-methylenebisacrylamide (0.2 mol%) to the above solution, stirring until completely dissolved to obtain a prepolymer solution, and the prepolymer solution is placed in a 40°C water bath for 72 hours to obtain the ion conductive hydrogel through free radical polymerization.

[0102] The elongation at break of the hydrogel in this embodiment is 882%, the tensile fracture stress is 0.79MP, and the toughness during stretching is 3.84MJ / m 3 ; When the compression reaches 80% compression strain, the compressive stress is 4.14MPa and the compression modulus is 403.19kPa; the swelling rate in water is 142%, the swelling rate in artificial sweat is 207%, and the swelling rate in artificial seawater is 18.2%; the conductivity is 1.43S / m.

[0103] Example 7

[0104] (1) dissolving acrylic acid (2.5 mol / L), acrylamide (2.5 mol / L), phytic acid (0.2 mol / L), and sodium carboxymethyl cellulose (5.0 mg / mL) in deionized water and mixing well to obtain a precursor solution;

[0105] (2) treating the precursor solution with ultrasound for 30 minutes to remove bubbles;

[0106] (3) Adding an initiator 2-hydroxy-2-methyl-1-phenyl-1-propanone (0.05 mol%) and a crosslinker polyethylene glycol diacrylate (0.2 mol%) to the above solution, stirring until completely dissolved to obtain a prepolymer solution, and irradiating the prepolymer solution under ultraviolet light for 90 minutes to obtain the ion conductive hydrogel through free radical polymerization.

[0107] The elongation at break of the hydrogel in this embodiment is 875%, the tensile fracture stress is 0.53MP, and the toughness during stretching is 2.19MJ / m 3 ;

[0108] When the compression reaches 80% compression strain, the compressive stress is 3.53MPa and the compression modulus is 352.68kPa; the swelling rate in water is 150%, the swelling rate in artificial sweat is 210%, and the swelling rate in artificial seawater is 20.5%; the conductivity is 1.06S / m.

[0109] Comparative Example 1

[0110] Based on Example 1, phytic acid and sodium carboxymethyl cellulose were not added: acrylic acid (4 mol / L) and acrylamide (1 mol / L) were dissolved in deionized water, and mixed evenly to obtain a precursor solution;

[0111] The other conditions are the same as those in Example 1; the tensile properties, compression properties, swelling properties and conductivity properties are shown in Figure 2 , 3 , 4 and 6.

[0112] The elongation at break of the hydrogel is 829%, the tensile stress at break is 312.98 kPa, and the toughness during stretching is 1.45 MJ / m 3 ; When the compression reaches 80% compression strain, the compressive stress is 3.01MPa and the compression modulus is 427.66kPa; the swelling rate in water is 200%; the conductivity is 0.13S / m.

[0113] It can be seen that compared with Example 1, the strength and toughness of the hydrogel in Comparative Example 1 are significantly reduced, the anti-swelling effect is poor, and the conductive property is weak.

[0114] Comparative Example 2

[0115] Based on Example 1, phytic acid was not added: acrylic acid (4 mol / L), acrylamide (1 mol / L), and sodium carboxymethyl cellulose (11.1 mg / mL) were dissolved in deionized water and mixed evenly to obtain a precursor solution; other conditions were the same as in Example 1. The tensile properties, compression properties, swelling properties, and conductive properties were shown in Table 1. Figure 2 , 3 , 4 and 6.

[0116] The elongation at break of the hydrogel is 695%, the tensile breaking stress is 323.56 kPa, and the toughness during stretching is 1.42 MJ / m 3 ; When the compression reaches 80% compression strain, the compressive stress is 4.00MPa and the compression modulus is 580.21kPa; the swelling rate in water is 446%; the conductivity is 0.09S / m.

[0117] It can be seen that compared with Example 1, the strength and toughness of the hydrogel in Comparative Example 2 are significantly reduced, the anti-swelling effect is poor, and the conductive property is weak.

[0118] Comparative Example 3

[0119] Based on Example 1, without adding sodium carboxymethyl cellulose: acrylic acid (4 mol / L), acrylamide (1 mol / L), and phytic acid (0.4 mol / L) were dissolved in deionized water and mixed uniformly to obtain a precursor solution;

[0120] Other conditions are the same as in Example 1;

[0121] Its tensile properties, compressive properties, swelling properties and conductive properties are shown in Figure 2 , 3 , 4 and 6.

[0122] The elongation at break of the hydrogel is 1178%, the tensile stress at break is 1.09 MPa, and the toughness during stretching is 5.95 MJ / m 3 When the compression reaches 80% compression strain, the compression stress is 5.98MPa and the compression modulus is 606.33kPa; the swelling rate in water is 496%; the conductivity is 2.51S / m. It can be seen that compared with Example 1, the conductivity of the hydrogel in Comparative Example 3 is equivalent, the strength and toughness are reduced, and the anti-swelling effect is poor.

[0123] Comparative Example 4

[0124] On the basis of Example 1, sodium carboxymethyl cellulose was not added, and the amount of sodium carboxymethyl cellulose added was converted into phytic acid for addition. The calculated concentration of phytic acid was 0.42 mol / L, as follows:

[0125] Dissolve acrylic acid (4 mol / L), acrylamide (1 mol / L), and phytic acid (0.42 mol / L) in deionized water, mix well, and obtain a precursor solution;

[0126] Other conditions are the same as in Example 1. Its tensile properties, compression properties, swelling properties and conductive properties are shown in Figure 2 , 3 and 6.

[0127] The elongation at break of the hydrogel is 1118%, the tensile stress at break is 1.25MPa, and the toughness during stretching is 7.28MJ / m 3 When the compression reaches 80% compression strain, the compression stress is 6.67MPa and the compression modulus is 615.35kPa; the swelling rate in water is 538%; the conductivity is 2.63S / m. It can be seen that compared with Example 1, the conductivity of the hydrogel in Comparative Example 4 is equivalent, the strength and toughness are reduced, and the anti-swelling effect is poor.

[0128] Comparative Example 5

[0129] Based on Example 1, phytic acid was not added, and the amount of phytic acid added was converted into sodium carboxymethyl cellulose. The added concentration of carboxymethyl cellulose was calculated to be 275.1 mg / mL: Acrylic acid (4 mol / L), acrylamide (1 mol / L), and sodium carboxymethyl cellulose (275.1 mg / mL) were dissolved in deionized water. It was found that they could not be completely dissolved, and the next step of the experiment could not be carried out. For details, see Fig. 9 .

[0130] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a high-toughness, low-swelling ion-conductive hydrogel, characterized in that: include, Dissolve acrylic acid, acrylamide, phytic acid and sodium carboxymethyl cellulose in deionized water, mix well, and obtain a precursor solution; removing bubbles from the precursor solution to obtain a precursor solution from which bubbles are removed; Adding an initiator and a cross-linking agent to the precursor solution from which bubbles have been removed, stirring until completely dissolved, to obtain a prepolymer solution; The prepolymer solution is free radical polymerized under preset conditions to obtain an ion conductive hydrogel with high strength, toughness and low swelling.

2. The preparation method according to claim 1, characterized in that: The free radical polymerization method includes at least one of temperature-induced free radical polymerization and light-induced free radical polymerization.

3. The preparation method according to claim 1 or 2, characterized in that: The concentration of acrylic acid in the precursor solution is 2.5-4 mol / L, the concentration of acrylamide in the precursor solution is 1-2.5 mol / L, the concentration of phytic acid in the precursor solution is 0.2-0.4 mol / L, and the concentration of sodium carboxymethyl cellulose in the precursor solution is 5.0-18.0 mg / mL; The total concentration of acrylic acid and acrylamide in the precursor solution is 5 mol / L.

4. The preparation method according to claim 3, characterized in that: The initiator is 0.05-0.4 mol% of the total molar amount of acrylic acid and acrylamide.

5. The preparation method according to claim 4, characterized in that: The initiator comprises a free radical polymerization initiator selected from at least one of ammonium persulfate, potassium persulfate and 2-hydroxy-2-methyl-1-phenyl-1-propanone.

6. The preparation method according to claim 5, characterized in that: The cross-linking agent includes a cross-linking agent with a double bond at the terminal group, and is selected from at least one of polyethylene glycol diacrylate and N,N'-methylenebisacrylamide.

7. The preparation method according to claim 6, characterized in that: The cross-linking agent is 0.05-0.2 mol% of the total molar amount of acrylic acid and acrylamide.

8. The method of any one of claims 1 to 7 to obtain an ion-conductive hydrogel with high toughness and low swelling, characterized in that: The hydrogel has a tensile elongation at break of 875-1082%, a tensile stress at break of 0.53-2.05 MPa, and a toughness during stretching of 2.19-10.57 MJ / m 3 ; When the compression reaches 80% strain, the compressive stress is 3.53-8.00 MPa and the compression modulus is 352.68-663.28 kPa; The swelling rate of the hydrogel in water is 100% to 150%; The tensile elongation at break of the hydrogel after swelling in water is 612-805%, and the tensile stress at break is 326-613 kPa; The swelling rate of the hydrogel in artificial sweat is 160-215%; The swelling rate of the hydrogel in artificial seawater is 8.0% to 20.5%; The conductivity of the ion conductive hydrogel is 1.06 to 2.39 S / m.

9. Use of the high-toughness, low-swelling ion-conductive hydrogel according to claim 8 in a sensor, characterized in that: The sensor includes a flexible sensor.

10. Use of the high-toughness, low-swelling ion-conductive hydrogel according to claim 8 in the preparation of wearable devices.

Citation Information

Patent Citations

  • Ion-covalent double-network hydrogel and preparation method thereof

    CN105461945A

  • Preparation method of polyacrylamide-sodium carboxymethylcellulose double-network transparent ionic conductive gel

    CN110092919A

  • Ionized water gel, ion thermoelectric device and preparation method and application thereof

    CN115697014A

  • Multifunctional ionic conductive high-toughness hydrogel as well as preparation method and application thereof

    CN115819684A

  • Carboxymethyl cellulose-based flexible wearable hydrogel material as well as preparation method and application thereof

    CN118772324A

Cited By

  • High-strength and high-toughness polymer hydrogel as well as preparation method and application thereof

    CN120757691A

  • A high-strength, high-toughness polymer hydrogel, its preparation method and application

    CN120757691B